The Master Hoof (Claw) Care Program: Summary Statistics From Three Years - Jan K. Shearer; S. R. Van Amstel; A. Gonzalez-Sagues; L. C. Shearer (EDIS, 2004)
In 1996, through a grant from the Florida dairy farmers, the Master Hoof Care Program was developed at the University of Florida. The objective of this program was (and is) to train dairy health care technicians and others in proper methods of foot care and claw trimming. The program is offered three times per year at the University of Florida and once annually at the University of Tennessee. This document is VM145, one of a series of the College of Veterinary Medicine-Large Animal Clinical Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 7, 2002.